Preoperative Collateral Perfusion Using Arterial Spin Labeling: A Predictor of Surgical Collaterals in Moyamoya Angiopathy - Wang, Maoxue; Wang, Yi; Zhang, Wen; Zhao, Xiance; Yang, Yongbo; Zhang, Bing (Frontiers in Neuroscience, 2022)
Objectives: Various degrees of surgical collateral circulation are often found in moyamoya angiopathy (MMA) patients after revascularization. Little is known about arterial spin labeling (ASL) that affects surgical collateral circulation. The aim of this study was to investigate the effect of ASL on surgical collaterals in patients with MMA after combined bypass surgery. Methods: MMA patients with complete radiological and clinical information, who had undergone combined bypass, were enrolled in this study. Surgical collaterals were classified as good or poor based on the Matsushima standard. Cerebral perfusion on ASL was quantitatively analyzed as relative cerebral blood flow (rCBF). The qualitative collateral score was calculated using a 4-grade scale. Univariable and multivariable logistic regression was performed to identify the predictors for surgical collaterals after combined bypass. Results: In total, 66 hemispheres of 61 patients (47 years old ± 8.66) were prospectively included (29 and 37 hemispheres with good and poor surgical collaterals, respectively). The presurgical collateral score was significantly lower in patients with good surgical collaterals (13.72 scores ±7.83) than in those with poor surgical collaterals (19.16 scores ±6.65, P=0.005). The presurgical rCBF and modified Rankin scale (mRS) scores were not significantly different between the two groups (PrCBF=0.639, PmRS=0.590). The collateral score was significantly elevated (good: 13.72 scores ±7.83 vs 20.79 scores ±6.65, P<0.001; poor: 19.16 scores ±6.65 vs 22.84 scores ±5.06, P<0.001), and the mRS was reduced (good: 1.66 scores ±1.14 vs 0.52 scores ±0.83, P<0.001; poor: 1.49 scores ±0.90 vs 0.62 scores ±0.76, P<0.001) in patients after revascularization. Multivariable logistic regression showed that preoperative collateral scores (OR: 0.791; 95%CI: 0.695, 0.900; P<0.001), age (OR: 0.181; 95%CI: 0.039, 0.854; P=0.031), sex (OR: 0.154; 95%CI: 0.035, 0.676; P=0.013) and hypertension (OR: 0.167; 95%CI: 0.038, 0.736; P=0.018) were predictors of surgical collaterals after combined revascularization. Conclusions:The preoperative collateral score based on ASL could be a predictor for surgical collaterals in patients with MMA after combined bypass surgery. Combined with age, sex and hypertension, it may have a better predictive effect.